Development of Gradation Indicators for Achieving Competencies Specific Motion Skills Junior High School Floor Gymnastics - Humiyati Humiyati; Mashud Mashud; Syamsul Arifin (UNIVERSITAS NEGERI MAKASSAR, 2022)
This research was motivated by the similarity of floor gymnastics learning materials delivered by physical education teachers at each grade level, not based on mapping basic competencies at each grade level. In addition, based on the results of the needs analysis, shows that 100% of junior high school physical education teachers in Hulu Sungai Utara District need guidance on learning floor gymnastics based on basic competency gradations for each grade level. The purpose of the study was to develop a gradation of indicators of the achievement of specific movement skills in floor gymnastics in junior high school. The research methods used are research and development, with development procedures; 1) the pre-development stage, and 2) the development stage, which is from needs analysis, product development, and product testing, to the creation of the final product development. The subjects of the study were physical education teachers in the North River Upper District, which numbered 31 teachers. The instrument used in this development research is a questionnaire, while the data analysis technique is a quantitative descriptive analysis with percentages. The results of this development research based on product trials (expert tests, small group tests, and large group tests) resulted in the development of product indicators of gradation indicators of achievement of floor gymnastics-specific movement skills.